2015
DOI: 10.1371/journal.pone.0121956
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Cholesterol Metabolism to a Negative Energy Balance in Dairy Cows Depends on the Lactational Stage

Abstract: The response of cholesterol metabolism to a negative energy balance (NEB) induced by feed restriction for 3 weeks starting at 100 days in milk (DIM) compared to the physiologically occurring NEB in week 1 postpartum (p.p.) was investigated in 50 dairy cows (25 control (CON) and 25 feed-restricted (RES)). Blood samples, liver biopsies and milk samples were taken in week 1 p.p., and in weeks 0 and 3 of feed restriction. Plasma concentrations of total cholesterol (C), phospholipids (PL), triglycerides (TAG), very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 41 publications
(78 reference statements)
5
35
1
1
Order By: Relevance
“…The remaining free fatty acids will be re-esterified to triglycerides (TG) and exported as VLDL to the plasma (Fig. 1) [50,74]. Van den Top et al [150] and Kessler et al [74] showed that plasma VLDL-cholesterol, LPL- [150].…”
Section: Oxidation Of Fatty Acids In Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining free fatty acids will be re-esterified to triglycerides (TG) and exported as VLDL to the plasma (Fig. 1) [50,74]. Van den Top et al [150] and Kessler et al [74] showed that plasma VLDL-cholesterol, LPL- [150].…”
Section: Oxidation Of Fatty Acids In Mitochondriamentioning
confidence: 99%
“…Kessler et al [74] showed that there is a significant correlation between SREBF2 mRNA expression and the hepatic gene expression of both 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) and HMGCS1. In addition, several investigations showed that occurrence of fatty liver syndrome early in lactation is associated with cholesterol carrier lipoproteins such as VLDL [50,74]. Cholesterol is transported by high density lipoproteins (HDL) from peripheral tissues to the liver [74].…”
Section: Genes and Key Pathways Regulating Liver Lipid And Cholesteromentioning
confidence: 99%
“…Indeed, the lower availability of plasma TG could decrease the need for the migration of mammary LPL toward the basal membrane for uptake by MG and could increase the flow of LPL toward the apical membrane and milk in cows, in contrast to goats . In ruminants, the TG in the plasma lipids are mainly of intestinal rather than hepatic origin, even if the liver conserves some capacity to synthesize TG that are secreted in VLDL in mid‐lactation . Plasma TG concentration depends on the physiological state of the animals, being higher in dry‐pregnant than in lactating ruminants and being higher at the end of lactation than at the beginning .…”
Section: Discussionmentioning
confidence: 99%
“…The cholesterol concentration indirectly reveals the ability of the liver to produce VLDLs (very low density lipoproteins) and decreased cholesterol and triglycerides are sign of fatty liver [30,31] . Gross et al [32] showed that change in lipid metabolic parameters during starvation is depends on lactation stage. During early lactation we have decrease of cholesterol and triglyceride concentration, but in later period concentration of this parameters increase during feed restriction.…”
Section: Discussionmentioning
confidence: 99%